(untitled) (Research, Society and Development, 2021)
Issues related to gender, in recent times, have been prominent in social discussions and in the strengthening of women’s struggle for their rights, especially those that make direct reference to equality between men and women and the non-acceptance of violence. As a result of a society marked by chauvinism arising from a patriarchal culture, violence has been very common in affective relationships, something that must be constantly combated. In the meantime, the objective of this work is to analyze the issues of gender and chauvinism present in the short story The right to not love, by Lygia Fagundes Telles, and the discursive positions that emerge in it. For this, we make use of bibliographic research, from the literary review, and the didactic sequence model proposed by Cosson (2011). From the analysis of the short story, in the light of the theory used, the results indicate that, although we are in the 21st century, in a society totally opposite to the patriarchal society, remnants of patriarchy are still quite evident in the relations between men and women, as can be seen infer from the daily scenes that take place in relationships, as shown in the figures in the didactic sequence. As a conclusion, the study indicates that, although the laws are in favor of women, they still need to fight hard to fully enjoy their social rights.